2015
DOI: 10.6061/clinics/2015(07)08
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ethyl pyruvate on leukocyte-endothelial interactions in the mesenteric microcirculation during early sepsis treatment

Abstract: OBJECTIVES:Experimental studies on sepsis have demonstrated that ethyl pyruvate is endowed with antioxidant and anti-inflammatory properties. This study aimed to investigate the effects of ethyl pyruvate on leukocyte-endothelial interactions in the mesenteric microcirculation in a live Escherichia coli-induced sepsis model in rats.METHODS:Male Wistar rats were administered an intravenous suspension of E. coli bacteria or were subjected to a sham procedure. Three hours after bacterial infusion, the rats were ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 32 publications
(33 reference statements)
0
5
0
Order By: Relevance
“…Thus, the data suggest, that TxT+H/R-induced systemic activation can be diminished by EtP, subsequently reducing the transmigration of neutrophils to sites of inflammation upon a traumatic insult. Moreover, in a model of E. coli -induced sepsis, treatment with EtP significantly diminished inflammation by reduced systemic leukocyte rolling, adherence and migration in the mesenteric microcirculation ( 63 ). In the present study, resuscitation with EtP reduced the expression of CD11b on circulating neutrophils, indicating at an anti-inflammatory effect via inhibition of systemic activation of leukocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the data suggest, that TxT+H/R-induced systemic activation can be diminished by EtP, subsequently reducing the transmigration of neutrophils to sites of inflammation upon a traumatic insult. Moreover, in a model of E. coli -induced sepsis, treatment with EtP significantly diminished inflammation by reduced systemic leukocyte rolling, adherence and migration in the mesenteric microcirculation ( 63 ). In the present study, resuscitation with EtP reduced the expression of CD11b on circulating neutrophils, indicating at an anti-inflammatory effect via inhibition of systemic activation of leukocytes.…”
Section: Discussionmentioning
confidence: 99%
“…The slides were mounted, and images were captured using an Olympus BX50 microscope equipped with a 3CCD Pro-series camera. The objects stained with AEC and DAB on the walls of mesenteric vessels were identified after threshold determination, and the stained area was quantified using an image analyzer (NIS-elements; Nikon, Tokyo, Japan [ 24 ].…”
Section: Methodsmentioning
confidence: 99%
“…Numerous studies have shown that the beneficial effects of EP in animal models of sepsis were related to its HMGB1-inhibiting activity [ 22 , 89 , 90 ]. Further, EP efficiently reduced the inflammation in the mesenteric microcirculation via downregulation of P-selectin and intercellular adhesion molecule-1 (ICAM-1) in septic rats [ 91 ]. In a cecal ligation and puncture (CLP) model of sepsis, EP was shown to reduce the mortality of rats, and it also reduced mitochondrial swelling and dysfunction, as well as the mitochondrial expression of aquaporin-8, a water channel protein that significantly contributed to mitochondrial swelling [ 92 ].…”
Section: Chemical David For the Autoimmune Goliathmentioning
confidence: 99%